Success Central: Implementing a Program to Meet the Needs of Diverse Learners in a Catholic High School - Laengle, SC, Teresa Marie; Redder, Deborah; Somers, Wilma; Sullivan, Kathryn (Catholic Education: A Journal of Inquiry and Practice, 2000)
Catholic high schools are among the most effective educational environments in the United States. Often celebrated as comprehensive and college preparatory, the typical Catholic high school boasts of its graduation rate, percentage of college-bound seniors, National Merit finalists, athletic prowess, and scholarship awards. This article pursues a relatively new theme for most Catholic high schools: creating an environment responsive to the needs of diverse learners. Following a school-within-a-school model, one Catholic high school in the Midwest designed and implemented a program to serve students with special needs. Their insights, struggles, and vision form the basis of this article which chronicles a success story worthy of replication.